Strengthening the Strategic and Operational Response for Reducing COVID-19 Transmission in Indonesia - Sutomo, Sumengen; Sagala, Salord; Sutomo, Bebi; Liem, William; Al Hamid, Hamzah (Kesmas, 2021)
Indonesia reported the first two cases of COVID-19 from Depok City, West Java, on March 2, 2020. This study aimed to evaluate the strategic response for reducing the COVID-19 transmission which mainly comprised case management, large-scale social restrictions, including micro-scale social restrictions, and the development of drugs and vaccines. The data were collected from the Indonesian Government’s official websites and the latest information from March 2020 to May 2021. A logical framework approach and a theory of change were used to describe, evaluate, and strengthen the strategic response. The current strategic response has not reduce the COVID-19 transmission. As of May 30, 2021, 1,879,730 confirmed cases with 101,639 active cases, 1,663,998 recovered, and 50,404 deaths have been reported from 34 provinces. The case management faced a high positive rate and case fatality. The large-scale social restrictions have not increased public awareness and behavior practice on the prevention and control. Currently, there is no cure, and the vaccination needs more time to complete. Strengthening the current strategic response needs more testing, contact tracing, better quality treatment, community education for behavior change, and effective vaccination.